Carnegie Institution of Washington reproductions collection - Carnegie Institution of Washington
Chiefly transcriptions and copies of documents in foreign archives and personal collections relating primarily to the history of the United States, especially the early Spanish period, and to British ministers to the U.S. from 1791 to 1812. Subjects include European treaties; Yucatan, Mexico; John C. Calhoun; and John White. Includes notes of Carnegie Institution members Francis S. Philbrick and Reuben Gold Thwaites. Collected for use in publication projects of the Carnegie Institution of Washington including the Descriptive Catalogue of the Documents Relating to the History of the United States in the Papeles Procedentes de Cuba Deposited in the Archivo General de Indias at Seville (1916) and Instructions to the British Ministers to the United States, 1791-1812 (1941).
In part, transcriptions and copies of originals in British, Dutch, Mexican, Scandinavian, and Spanish repositories and private collections
Collection material in English, Danish, Dutch, Portuguese, Swedish, and other Scandinavian languages.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Calhoun, John C. -- 1782-1850.; Philbrick, Francis S. -- 1876-1970.; Thwaites, Reuben Gold, -- 1853-1913.; White, John, -- active 1585-1593.; Diplomatic and consular service, British -- United States; Europe -- Foreign relations -- United States; Great Britain -- Foreign relations -- United States; Spain -- Colonies -- America; United States -- Foreign relations -- Europe; United States -- Foreign relations -- Great Britain; United States -- History -- Colonial period, ca. 1600-1775.; Yucatán (Mexico : State) -- History